RESEARCH ON STORM WAVE CHARATERISTICS IN CENTRAL COAST OF VIETNAM - Long, Võ Duy; Tâm, Trần Thu (Vietnam Journal of Marine Science and Technology, 2014)
In this research, the numerical model was used to simulate the wind field, and then the wave field of the storm. Using historical best tracks of the storm, the characteristic waves along the coast have been collected after each storm simulation. In this way, we created long series of wave characteristics, and then the statistical method was used to obtain the probability distribution functions of the wave height. The results show that the Burr distribution function fitted well to simulated value of wave heights. The results written in form of popular Weibull distribution function are also showed for practical purpose. Furthermore, this research also determined the dangerous direction of wave in storm, based on the statistical characteristics of the wave storm.